DESALINATION AND BOREHOLE CONSTRUCTION FOR ABSTRACTION OF SALINE WATER AND CHANNELING BRINE DISPOSAL - Sampatakakis, P.; Manthos, G.; Kepas, A. (Bulletin of the Geological Society of Greece, 2016)
The purpose of this research is to present all the technical details, but also the scientific criteria according to which there is the possibility to make a borehole for the extraction of the saline water and channeling of brine in another borehole. This methodology has purpose to prove that this way of extraction of saline water (or sea water) through the borehole and the channeling of the remain into another one has multiple assets comparing to the classical method of the direct extraction and return of the residue into the sea. These assets are considered to be better because of the extraction which may be in the inland, hypsometrically more advantageous. Also, the channeling of the brine disposal in a nearby borehole is safer from an environmental point of view because does not disturb the flora and fauna in the benthic zone of the marine space, but also a less expensive solution than channeling it straight into the sea. In any case, it is a necessary presumption that the hydrogeologic conditions in the area where the work is taking place to ensure a high factor of permeability and hydraulic connection with the sea area. The application of this technique was completed with some success in the case of Agistri Island (and homonymous municipality) which is located in the Saronic Gulf, southwest of Salamis Island. Although the distance between the two boreholes should be larger in order to prevent the risk of dynamic input of brine disposal to the borehole extraction because of the radius of influence, which would destroy the osmosis membranes. After the appropriate evaluation of the test pumping elements, this was ensured by placing the appropriate sensors of salinity.